Endocrine Disorders and Genital Infections Impair Gynecological Health in APECED (APS-1) - Saari, Viivi; Laakso, Saila; Tiitinen, Aila; Mäkitie, Outi; Holopainen, Elina (Frontiers in Endocrinology, 2021)
Objective: In autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) defects in the autoimmune regulator gene lead to impaired immunotolerance. We explored the effects of immunodeficiency and endocrinopathies on gynecologic health in patients with APECED. Design: Cross-sectional cohort study combined with longitudinal follow-up data. Methods: We carried out a gynecologic evaluation, pelvic ultrasound, and laboratory and microbiologic assessment in 19 women with APECED. Retrospective data were collected from previous study visits and hospital records. Results: The study subjects’ median age was 42.6 years (range, 16.7-65.5). Sixteen patients (84%) had premature ovarian insufficiency, diagnosed at the median age of 16.5 years; 75% of them used currently either combined contraception or hormonal replacement therapy. In 76% of women, the morphology and size of the uterus were determined normal for age, menopausal status, and current hormonal therapy. Fifteen patients (79%) had primary adrenal insufficiency; three of them used dehydroepiandrosterone substitution. All androgen concentrations were under the detection limit in 11 patients (58%). Genital infections were detected in nine patients (47%); most of them were asymptomatic. Gynecologic C. albicans infection was detected in four patients (21%); one of the strains was resistant to azoles. Five patients (26%) had human papillomavirus infection, three of which were high-risk subtypes. Cervical cell atypia was detected in one patient. No correlation between genital infections and anti-cytokine autoantibodies was found. Conclusions: Ovarian and adrenal insufficiencies manifested with very low androgen levels in over half of the patients. Asymptomatic genital infections, but not cervical cell atypia, were common in female patients with APECED.